COVID-19 vaccine effectiveness among South Asians in Canada. - Rahul Chanchlani; Baiju R Shah; Shrikant I Bangdiwala; Russell J de Souza; Jin Luo; Shelly Bolotin; Dawn M E Bowdish; Dipika Desai; Karl Everett; Scott A Lear; Mark Loeb; Zubin Punthakee; et al. (PLOS Global Public Health)
We evaluated the effectiveness of COVID-19 vaccines among South Asians living in Ontario, Canada compared to non-South Asians and compared the odds of symptomatic COVID-19 infection and related hospitalizations and deaths among non-vaccinated South Asians and non-South Asians. This was a test negative design study conducted in Ontario, Canada between December 14, 2020 and November 15, 2021. All eligible individuals >18 years with symptoms of COVID-19 were subdivided by ethnicity (South Asian vs other) and vaccination status (vaccinated versus not). The primary outcome was vaccine effectiveness as defined by COVID-19 infections, hospitalizations, and deaths, and secondary outcome was the odds of COVID-19 infections, hospitalizations, and death comparing non-vaccinated South Asians to non-vaccinated non-South Asians. 883,155 individuals were included. Among South Asians, two doses of COVID-19 vaccine prevented 93.8% (95% CI 93.2, 94.4) of COVID-19 infections and 97.5% (95% CI 95.2, 98.6) of hospitalizations and deaths. Among non-South Asians, vaccines prevented 86.6% (CI 86.3, 86.9) of COVID-19 infections and 93.1% (CI 92.2, 93.8) of hospitalizations and deaths. Non-vaccinated South Asians had higher odds of symptomatic SARS-CoV-2 infection compared to non-vaccinated non-South Asians (OR 2.35, 95% CI 2.3, 2.4), regardless of their immigration status. COVID-19 vaccines are effective in preventing infections, hospitalizations and deaths among South Asians living in Canada. The observation that non-vaccinated South Asians have higher odds of symptomatic COVID-19 infection warrants further investigation.